Ketamine in Status Epilepticus: How Soon Is Now? - Giuseppe Magro (Neurology International)
Status epilepticus (SE) is a neurological emergency. Current evidence dictates a step-by-step approach with a first line of therapy consisting of benzodiazepines (BDZs). In many situations, the currently approved approach does not terminate a BDZ-resistant SE. This happens in Stage 1 Plus, a framework designed by the author to recognize cases of probable benzodiazepine-resistant status epilepticus even before treatment initiation. These cases include Prolonged SE (SE lasting > 10 min), the absence of prominent motor phenomena, and acute etiology (primary central nervous system etiologies most of all). BDZ-refractory SE cases (Stage 1 Plus) might require a different approach, one targeting the unresponsive GABA signaling state mediated by NMDA/AMPA receptors, such as combined polytherapy with Ketamine from the start. These considerations stem from the receptor trafficking hypotheses: in prolonged seizure activity and primary central nervous system etiologies, GABA receptors get internalized and move away from synapses, and therefore, SE becomes resistant to BDZ. A rational polytherapy that might restore the unresponsiveness to BDZ in SE should include NMDA antagonists, such as Ketamine. Ketamine has proven effective in many experimental models of status epilepticus, and much evidence is gathering supporting its use in humans, especially in refractory and super-refractory SE. We lack studies evaluating combined polytherapy in SE, especially in the early phases. The author suggests here that Ketamine should be used along with first-line BDZ in the early SE stage falling in the category of Stage 1 Plus and as a first-line anesthetic infusion drug in refractory SE, especially in cases progressing from Stage 1 Plus, eventually adding continuous midazolam/propofol infusion in later phases. This systematic review’s objective is to summarize the presently available evidence of the early use of combined polytherapy that includes Ketamine, along with the currently available evidence of Ketamine use in early, established, and refractory SE. Nine studies were included. Boluses of Ketamine and Midazolam are effective in pediatric convulsive Stage 1 Plus SE. The results show that earlier Ketamine administration (especially within 12 h of SE onset) was significantly associated with improved seizure control, with a more favorable safety profile than Midazolam in refractory SE. Notably, a dosage of less than 0.9 mg/kg/h proves ineffective in terminating SE. Ketamine has the advantage of preventing intubation, possibly shortening the length of stay in the intensive care unit.